1999
DOI: 10.1016/s0735-1097(99)00068-6
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of regional myocardial strain and work during ventricular pacing: experimental study using magnetic resonance imaging tagging

Abstract: Ventricular pacing causes a threefold difference in myofiber work within the LV wall. This difference appears large enough to regard local myocardial function as an important determinant for abnormalities in perfusion, metabolism, structure and pump function during asynchronous electrical activation. Pacing at sites that cause more synchronous activation may limit the occurrence of such derangements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

48
418
0
10

Year Published

2000
2000
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 601 publications
(476 citation statements)
references
References 30 publications
48
418
0
10
Order By: Relevance
“…Compared with the normal values (RA pacing), strain and external work during LV pacing were approximately zero in regions near the pacing site, and gradually increased to more than twice the normal value in remote regions. 51 These results are similar to our results for Fiber B without remodeling. With remodeling, we found a more homogeneous distribution of shortening and external work for Fibers A and B.…”
Section: Ventricular Electromechanicssupporting
confidence: 92%
See 4 more Smart Citations
“…Compared with the normal values (RA pacing), strain and external work during LV pacing were approximately zero in regions near the pacing site, and gradually increased to more than twice the normal value in remote regions. 51 These results are similar to our results for Fiber B without remodeling. With remodeling, we found a more homogeneous distribution of shortening and external work for Fibers A and B.…”
Section: Ventricular Electromechanicssupporting
confidence: 92%
“…In Fiber A, external work was almost homogeneous with remodeling (Fig. 6), which is in agreement with the measurements during RA pacing (normal stimulation) of Prinzen et al 51 Ashikaga et al 4 investigated transmural dispersion of mechanics in vivo. They found that the onset of myofiber shortening was earliest in the endocardial layers, while the onset of myofiber relaxation was latest in the endocardial layers.…”
Section: Ventricular Electromechanicssupporting
confidence: 88%
See 3 more Smart Citations